Ritual Ecology and Indigenous Environmental Knowledge: The Anderenat Tradition of Gili Iyang Island - Moh. Syaiful Bahri; Ghufron, Muhammad Ghufron (Faculty of Ushuluddin and Philosophy, 2025)
The Anderenat tradition is a ritual practice of the Gili Iyang community that articulates a complex relationship between spirituality, ecology, and social life. While commonly understood as a rain-invoking ceremony, this study argues that Anderenat functions more broadly as a cultural mechanism for negotiating human–nature relations in a context of environmental vulnerability. Drawing on cultural philosophy and cultural studies, this research analyzes ritual symbolism—particularly water, local plants, traditional music, and communal labor—as embodied forms of indigenous environmental knowledge and spiritual ethics. The analysis demonstrates that Anderenat operates as a site of ecological pedagogy, transmitting environmental values across generations while reinforcing collective identity and social solidarity. Moreover, the ritual reveals how local communities mobilize spiritual and cultural resources to respond to contemporary ecological and social transformations. By situating Anderenat within wider debates on ritual ecology and indigenous environmental knowledge, this study contributes to international discussions on how ritual practices function as culturally grounded responses to environmental sustainability beyond technocratic and policy-driven frameworks.